Preparing Latinx College Students for Leadership in California - Glickman, Ronald S. (Journal of Leadership, Accountability and Ethics, 2020)
With a majority Latinx population in California and the future of the state’s economy depending on college educated leaders, it is important to develop a deeper understanding of how Hispanic Serving Institutions (HSIs) in the state can better prepare Latinx students for leadership in the workforce. In this qualitative case study, the author investigated the experiences of four first-generation college students in an undergraduate leadership course at an HSI and their perceptions about how their experiences in the course influenced their beliefs about leadership and their behavior in the workforce.